Identification of velocity variations in a seismic cube using neural networks - Cersósimo, Diego Sergio (2006)
This research allow to infer that from seismic section and well data it is possible to determine velocity anomalies variations in layers with thicknesses below to the seismic resolution using neuronal networks.